Twenty-four-hour variation of vestibular function in young and elderly adults. (2nd January 2021) - Martin, Tristan; Zouabi, Amira; Pasquier, Florane; Denise, Pierre; Gauthier, Antoine; Quarck, Gaëlle
ABSTRACT: Animal and human studies demonstrate anatomical and functional links between the vestibular nuclei and the circadian timing system. This promotes the hypothesis of a circadian rhythm of vestibular function. The objective of this study was to evaluate the vestibular function through the vestibulo-ocular reflex using a rotatory chair at different times of the day to assess circadian rhythmicity of vestibular function. Two identical studies evaluating temporal variation of the vestibulo-ocular reflex (VOR) were performed, the first in young adults (age: 22.4 ± 1.5 y), and the second in older adults (70.7 ± 4.7 y). The slow phase velocity and time constant of the VOR were evaluated in six separate test sessions, i.e., 02:00, 06:00, 10:00, 14:00, 18:00, and 22:00 h. In both studies, markers of circadian rhythmicity (temperature, fatigue, and sleepiness) displayed expected usual temporal variation. In young adults, the time constant of the VOR showed variation throughout the day ( p < .005), being maximum 12:25 h (06:00 h test session) before the acrophase of temperature circadian rhythm. In older adults, the slow phase velocity and time constant also displayed temporal variation ( p < .05). Maximum values were recorded at 10:35 h (06:00 h test session) before the acrophase of temperature circadian rhythm. The present study demonstrates that vestibular function is not constant throughout the day. The implication of the temporal variation in vestibular system in equilibrium potentially exposes the elderly, in particular, to differential risk during the 24 h of losing balance and falling.